Feasibility Study of Renewable Energy Deployment Scenarios in Remote Arctic Communities - Nazarova, Yulia Alexandrovna; Sopilko, Natalya Yuryevna; Kulakov, Andrey Valentinovich; Shatalova, Irina Ivanovna; Myasnikova, Olga Yuryevna; Bondarchuk, Nataliya Vital’evna (International Journal of Energy Economics and Policy, 2018)
The paper aims to analyze the economic efficiency of investments in renewable energy in remote areas of the Russian Arctic. Despite the proximity to oil and gas wells, the development of renewable energy sources (RES) is most promising in these locations. The paper presents a feasibility study of two investment options based on RES with a calculation of electricity costs which ensure an expected return to potential investors. The estimation is given in comparison to the existing electricity rates in some communities of the Russian Arctic. The investigation revealed that the investment in RES is feasible but requires a proper technical and financial estimation. The estimation of undiscounted future cash flows may not be sufficient in case of long-term investments; high initial capital investments in RES are not always covered by lower operating costs. As a conclusion, the investment option of the wind-power plant with the system of accumulation and use of energy in the form of hydrogen, bound in a liquid organic carrier is less financially attractive due to high capital investments in comparison with the variant of wind-diesel deployment. The given calculations can provide an economic feasibility approach in finding the best option for RES deployment in remote Arctic areas. Keywords: Renewable energy, wind turbine, hydrogen energy carriers, diesel generation, the Russian Arctic. JEL Classification: Q4 DOI: https://doi.org/10.32479/ijeep.7343